Issues of National Education in the Educational Works of the Bukhara Jadids - Sayfulloevna, Ashurova Marhabo (International Journal on Integrated Education, 2024)
This article describes the variety of sciences in Bukhara and the methods of passing them, as well as the classification of existing sciences. This is proven by facts.